SAT0580 Association of childhood and adulthood adiposity measures with knee cartilage thickness, cartilage volume and bone area in young adults. (12th June 2018) - Meng, T.; Venn, A.; Eckstein, F.; Wirth, W.; Cicuttini, F.; March, L.; Dwyer, T.; Cross, M.; Laslett, L.L.; Jones, G.; Ding, C.; Antony, B.
Abstract : Background: Adiposity is associated with increased risk of knee osteoarthritis (OA); cartilage thickness, cartilage volume and subchondral bone area are established biomarkers in knee OA. However, there are no studies describing the effects of adiposity during early life on knee cartilage and bone morphology in adulthood. Objectives: To describe the longitudinal associations between adiposity measures in childhood and adulthood and knee cartilage thickness, cartilage volume and subchondral bone area in young adults. Methods: 186 participants from the Australian Schools Health and Fitness Survey of 1985 (aged 7–15 years) were followed up 25 years later (aged 31–40 years). Childhood measures (weight, height, waist circumference and hip circumference) were collected in 1985, and corresponding adulthood measures were collected during 2004–2006. Body mass index (BMI) and waist-hip ratio (WHR) were calculated. Participants underwent knee magnetic resonance imaging (MRI) during 2008–2010, and cartilage thickness, cartilage volume and subchondral bone area were measured using a quantitative approach (Chondrometrics 3.0, Germany). Multivariable linear regressions were used to examine the above associations. Results: Among 186 participants (48.4% females), 7.6% were overweight in childhood, and 42.1% in adulthood. There were no significant associations between childhood adiposity measures and adulthood knee cartilage and bone morphological measures; the same applied to adulthood BMI and overweight. However, adulthood WHR was negatively associated with cartilage thickness in the patella (β −0.009 mm/0.01 unit, 95% confidence interval (CI) −0.019 to 0.001, p=0.065), the medial femorotibial compartment (MFTC) (−0.011, –0.022 to 0.000, p=0.048) and the lateral femorotibial compartment (LFTC) (−0.013, –0.025 to −0.002, p=0.027), with cartilage volume in the patella (β −21.85 mm 3 /0.01 unit, 95% CI −37.77 to −5.93, p=0.007), the MFTC (−14.17, –29.53 to 1.19, p=0.070) and the LFTC (−23.87, –42.18 to −5.57, p=0.011), and with subchondral bone area in the patella (β −4.69 mm 2 /0.01 unit, 95% CI −8.26 to −1.12, p=0.010) and the LFTC (−4.76, –9.47 to −0.06, p=0.047), but not the MFTC. Linear regression lines are from models adjusted for adulthood age, duration of follow-up, gender and adulthood knee injury. WHR, waist-hip ratio; MFTC, medial femorotibial compartment; LFTC, lateral femorotibial compartment. Conclusions: Childhood adiposity measures did not predict adulthood knee cartilage and bone morphological measures. However, adulthood WHR, but not BMI or overweight status, was negatively associated with cartilage thickness, cartilage volume and subchondral bone area, suggesting central obesity may affect knee structures in young adults. Disclosure of Interest: None declared